wood sculptures of the maconde people album - Instituto de investigacao cientifica de Mocambique (Maputo, 1963)
Album Edited by the instituto de investigacao cientifica de mocambique to celebrate the fiftieth anniversary of the museum dr alvaro de castro
Keywords: investigacao cientifica